2014
DOI: 10.1089/cyber.2014.0098
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-Face or Not-to-Face: A Technology Preference for Communication

Abstract: This study employed the Model of Technology Preference (MTP) to explain the relationship of the variables as the antecedents of behavioral intention to adopt a social networking site (SNS) for communication. Selfadministered questionnaires were distributed to SNS account users using paper-based and web-based surveys that led to 514 valid responses. The data were analyzed using structural equation modeling (SEM). The results show that two out of three attributes of the attribute-based preference (ATRP) affect a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Recent technological advancements in electronic devices and remote communication options, such as mobile phones, have dramatically impacted the way individuals communicate in daily life [1]. To participate in civil society today, it is necessary to use mobile phones to communicate with unknown people in a variety of situations.…”
Section: Introductionmentioning
confidence: 99%
“…Recent technological advancements in electronic devices and remote communication options, such as mobile phones, have dramatically impacted the way individuals communicate in daily life [1]. To participate in civil society today, it is necessary to use mobile phones to communicate with unknown people in a variety of situations.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the interviews is to further understand the effect of social presence and perceived enjoyment towards the attitude applied while using SNS for communication. Data from the previous study (Jaafar et al, 2014) suggested that social presence and perceived enjoyment affected one's attitude toward using SNS communication in the presence of an alternative FtF communication among SNS users.The targeted population of this study is Malaysians with SNS accounts. The study applied the purposive sampling technique.…”
mentioning
confidence: 96%